Online processing system of business permit or license of local government units (OPSBPL-LGUs) - Ladres, Johanna Rizza P. (2010)
Business registration in most of the local government units in the Philippines are still done manually. This process is inefficient and cause inconvenience to the business permit applicants. With this problem, this project called Online Processing System of Business Permit or License of Local Government Units (OPSBPL-LGUs) was developed to automate the process of business registration. Through this system, it is anticipated that it could provide a more convenient way for the business owners to apply for business permits and have their business registered. The users of the system are limited to the licensing officers, regulatory officers, collection officers, and system administrator. The system administrator is responsible for the maintenance of the files of the system. The licensing officers are responsible for the process of registration of business and printing of necessary forms. The regulatory officers are responsible for the approval or disapproval of the business permit application. The collection officer is responsible for the collection of payments. The data that were used to test the system, though hypothetical, are patterned on actual processing of business permit and license. The results of each process are presented in tabular form for each user interface. The system curtailed the processing time since the applicant will no longer fill-out multiple application forms. There will be no travel required for the applicants to the different district offices nor the regulatory offices since each regulatory officer will have his own interface. The system is nearly paperless; thus, it could be a potential savings for the local government
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: Business permit; Business; Permit; License; Online processing system; Local government units